ANALISIS TINGKAT EFEKTIVITAS PAJAK HIBURAN DI KABUPATEN PASURUAN TAHUN 2009-2013 - ROSATIA SARI, MANASHA Rosatia (Jurnal Akuntansi AKUNESA, 2014)
The Local Genuine Income called PAD is a source of local income which may consist of local tax,local retribution, separated local wealth management, and others. Entertainment Tax is local taxcomponent.Entertainment is a potential sector for improvement of Pasuruan local revenue. Theobjective of research is to understand the contribution, effectiveness and growth rates ofentertainment taxes to Local Genuine Income called PAD. This research be expected can providebenefit and input for the local government of Pasuruan.the object of this research is EntertainmentTax acceptance in Pasuruan about 2009-2013. Method data collection who used in this researchis secondary data. Method data analyze who used contribution, effectiveness and growth rate.Based of the result, show that the average contribution rate of entertainment tax to Local GenuineIncome is 2,07%. The effectiveness rate of Entertainment Tax is 125,24% and the average ofgrowth rate of Entertainment Tax is 35,04%.Keywords: Local Genuine Income, Local Tax, Entertainment Tax, Contribution, Effectiveness,Growth Rate.